Louise Fili inspiration and process in design - Fili, Louise 1951- (Moleskine Books, Princeton Architectural Press, 2021)
Renowned graphic designer and author Louise Fili takes us on a personal tour through her most famous brands, books, and packaging. This peek behind-the-scenes shows how research and vintage typography give rise to her unique and ingenious designs. See how her work-still done by hand-transforms from early sketches to final design. Her instantly recognizable style, elegant and timeless, takes shape on the page before our eyes. Also included are Fili's copyright pages, which are works of art in their own right. All content appears in print for the first time
Keywords: Fili, Louise -- 1951-; Grafikdesign; Marke; Fili, Louise / Catalogs; Fili, Louise / Themes, motives; Fili, Louise / Sources; Fili, Louise; Graphic arts; Graphic artists; Women designers; Themes, motives; Catalogs; Sources; Bildband